Obstáculos en la evaluación diagnóstica : Una propuesta de superación mediante la identificación de modelos presentes en el curso - Espíndola, Carlos (2012)
The knowledge of student's representations constitutes a fundamental element in teaching planning. When a great number of data must be considered, knowledge of the diversity of representations in the classroom may be difficult. The teacher ́s usual point of view, required for certification of knowledge, seems not to be an adequate scheme in these cases. In this article we show an alternative diagnostic assessment technique based on a phenomenographic frame which gives a way to the identification of alternative ideas together with a comparative analysis with traditional evaluation methods. The shown phenomenographic based technique not only provides an option to the quality control point of view held in the traditional assessment scheme but also a useful tool in the detection of representations.